The role of spermatozoa-zona pellucida interaction in selecting fertilization-competent spermatozoa in humans - Leung, Erica T. Y.; Lee, Brayden K. M.; Lee, Cheuk-Lun; Tian, Xinyi; Lam, Kevin K. W.; Li, Raymond H. W.; Ng, Ernest H. Y.; Yeung, William S. B.; Ou, Jian-Ping; Chiu, Philip C. N. (Frontiers in Endocrinology, 2023)
Human fertilization begins when a capacitated spermatozoon binds to the zona pellucida (ZP) surrounding a mature oocyte. Defective spermatozoa-ZP interaction contributes to male infertility and is a leading cause of reduced fertilization rates in assisted reproduction treatments (ARTs). Human ejaculate contains millions of spermatozoa with varying degrees of fertilization potential and genetic quality, of which only thousands of motile spermatozoa can bind to the ZP at the fertilization site. This observation suggests that human ZP selectively interacts with competitively superior spermatozoa characterized by high fertilizing capability and genetic integrity. However, direct evidence for ZP-mediated sperm selection process is lacking. This study aims to demonstrate that spermatozoa-ZP interaction represents a crucial step in selecting fertilization-competent spermatozoa in humans. ZP-bound and unbound spermatozoa were respectively collected by a spermatozoa-ZP coincubation assay. The time-course data demonstrated that ZP interacted with a small proportion of motile spermatozoa. Heat shock 70 kDa protein 2 (HSPA2) and sperm acrosome associated 3 (SPACA 3) are two protein markers associated with the sperm ZP-binding ability. Immunofluorescent staining indicated that the ZP-bound spermatozoa had significantly higher expression levels of HSPA2 and SPACA3 than the unbound spermatozoa. ZP-bound spermatozoa had a significantly higher level of normal morphology, DNA integrity, chromatin integrity, protamination and global methylation when compared to the unbound spermatozoa. The results validated the possibility of applying spermatozoa-ZP interaction to select fertilization-competent spermatozoa in ART. This highly selective interaction might also provide diagnostic information regarding the fertilization potential and genetic qualities of spermatozoa independent of those derived from the standard semen analysis.